2010
DOI: 10.1097/dbp.0b013e3181cc7cbc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Perinatal Adversities on Tic Severity and Symptoms of Attention Deficit/Hyperactivity Disorder in Children and Adolescents With a Tic Disorder

Abstract: This study provides evidence of a role for perinatal adversities in the etiology of tic disorders. Children with perinatal adversities may be vulnerable to develop more severe tics or comorbid ADHD symptoms in the presence of a positive family history of mental disorders, suggesting a role for gene-environment interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 30 publications
2
27
1
1
Order By: Relevance
“…Pregnancy complications which included hypertension, infections, (pre)eclampsia, psychosocial stress, or diabetes mellitus were reported to be associated with greater tic severity at a single time point as measured by the Yale Global Tic Severity Scale (YGTSS) [27]. However, these pregnancy complications were found to be associated with lower mean compulsive CYBOCS ratings in these patients [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy complications which included hypertension, infections, (pre)eclampsia, psychosocial stress, or diabetes mellitus were reported to be associated with greater tic severity at a single time point as measured by the Yale Global Tic Severity Scale (YGTSS) [27]. However, these pregnancy complications were found to be associated with lower mean compulsive CYBOCS ratings in these patients [28].…”
Section: Resultsmentioning
confidence: 99%
“…More severe ADHD rating scale scores, measured with the parent version of the ADHD Rating Scale, were associated with maternal smoking (smoking versus non-smoking: 26.4 ± 10.1 versus 19.1 ± 10.9, p = 0.05) [27]. This association was more prominent when there was a positive family history of mental disorders (p = 0.04) [27].…”
Section: Resultsmentioning
confidence: 99%
“…Smoking during pregnancy has been related to neurodevelopmental disorders, including ADHD [13][14][15][16][17][18][19][20]. Prenatal maternal smoking has been associated with increased tic severity [21] and comorbid ADHD or OCD [22,23], but the studies are few with inconsistent results [21][22][23][24][25]. The inconsistencies could be explained by relatively small sample sizes, retrospective data collection, limited consideration for confounding factors, inconsistent study populations and outcome definitions [3,4,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 86%
“…Gene-environmental interactions in the etiology of TS have not been a major focus of research yet. However, BosVeneman et al [24] suggested that the relationship between in utero smoking exposure and ADHD symptom severity in children with TS or chronic tic disorder was more pronounced in children with a positive family history of mental disorders. This could indicate that gene-environmental interactions affect the TS/ADHD phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…To address genetic confounds, genetically-sensitive designs are needed to estimate the relative contributions of genetic factors and smoking during pregnancy. The results from D'Onofrio et al [78], Lindblad and Hjern [80], BosVeneman et al [81] suggest that the relationship between prenatal tobacco smoke exposure and ADHD may be influenced and/or confounded by familial factors, such as family history of mental disorders. As the example, the analysis based on large Swedish population-based cohort indicated dose-dependent relationship between foetal exposure to tobacco constituents assessed prospectively at prenatal visit and the risk of ADHD medications use in children at 6-19 years of age (OR = 1.9; 95% CI: 1.8-2.0 for the children of mothers who smoked ≥ 10 cigarettes per day during pregnancy in the entire study population) [80].…”
Section: Alcohol and Adhd Or Adhd Symptomsmentioning
confidence: 94%